Learning how to learn : how to succeed in school without spending all your time studying - Oakley, Barbara A., 1955-; Sejnowski, Terrence J. (Terrence Joseph); McConville, Alistair (TarcherPerigee, 2018)
Presents advice for learning how to learn and master almost any skill, discussing the tools that are in everyone's minds already and how to begin using them effectively, through strategies like letting one's mind wander as a way of jump-starting the learning process, as well as offering a powerful tool to stop procrastinating.